Public and private enforcement of securities laws : the regulator and the class action in Australia's continuous disclosure regime - Legg, Michael (London [England] : Hart Publishing, 2022)
"This book undertakes unique case studies, including interviews with participants, as well as empirical analysis, of public and private enforcement of Australian securities laws addressing continuous disclosure. Enforcement of laws is crucial to effective regulation. Historically, enforcement was the province of a government regulator with significant discretion (public enforcement). However, more and more citizens are being expected to take action themselves (private enforcement). Consistent with regulatory pluralism, public and private enforcement exist in parallel, with the capacity to both help and hinder each other, and the achievement of the goals of enforcement in a range of areas of regulation. The rise of the shareholder class action in Australia, backed by litigation funding or lawyers, has given rise to enforcement overlapping with that of the government regulator, the Australian Securities and Investments Commission. The ramifications of overlapping enforcement are explained based on detailed analysis. The analysis is further bolstered by the regulator's approach to enforcement changing from a compliance orientation to a "Why not litigate?" approach. The analysis and ramifications of the Australian case studies involve matters of regulatory theory and practice that apply across jurisdictions. The book will appeal to practitioners, regulators and academics interested in regulatory policy and enforcement, and the operation of regulators and class actions, including their interaction."--
1. Introduction -- 2. Background -- 3. Analytical Framework -- 4. Case Studies -- 5. Application of the Analytical Framework to the Case Studies -- 6. Effectiveness and Co-existence of Regulatory Enforcement and Class Actions -- 7. Public and Private Enforcement Recalibrated -- 8. Co-ordination of Public and Private Enforcement
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Securities -- State supervision -- Australia; Securities industry -- Law and legislation -- Australia; Stock exchanges -- Law and legislation -- Australia; Electronic books